Virtual Genome Scan: A Tool for Restriction Landmark-Based Scanning of the Human Genome - Rouillard, Jean-Marie; Erson, Ayse E.; Kuick, Rork; Asakawa, Jun-ichi; Wimmer, Katharina; Muleris, Martine; Petty, Elizabeth M.; Hanash, Samir (Genome Research, 2001)
There is substantial interest in implementing technologies that allow comparisons of whole genomes of individuals and of tissues and cell populations. Restriction landmark genome scanning (RLGS) is a highly resolving gel-based technique in which several thousand fragments in genomic digests are visualized simultaneously and quantitatively analyzed. The widespread use of RLGS has been hampered by difficulty in deriving sequence information for displayed fragments and a lack of whole-genome sequence-based framework for interpreting RLGS patterns. We have developed informatics tools for comparisons of sample derived RLGS patterns with patterns predicted from the human genome sequence and displayed as Virtual Genome Scans (VGS). The tools developed allow sequence prediction of fragments in RLGS patterns obtained with different restriction enzyme combinations. The utility of VGS is demonstrated by the identification of restriction fragment length polymorphisms, and of amplifications, deletions, and methylation changes in tumor-derived CpG islands and the characterization of an amplified region in a breast tumor that spanned <230 kb on 17q23.